2017
DOI: 10.1158/0008-5472.can-16-2621
|View full text |Cite|
|
Sign up to set email alerts
|

ARF Confers a Context-Dependent Response to Chemotherapy in Muscle-Invasive Bladder Cancer

Abstract: Muscle invasive bladder cancer (MIBC) generally responds poorly to treatment and tends to exhibit significant mortality. Here we show that expression of the tumor suppressor p14ARF (ARF) is upregulated in aggressive subtypes of MIBC. Accumulation of ARF in the nucleolus is associated with poor outcome and attenuated response to chemotherapy. In both genetically-engineered mouse (GEM) models and murine xenograft models of human MIBC, we demonstrate that tumors expressing ARF failed to respond to treatment with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Interestingly, a substantial percentage (35%) of MIBCs, displays mutant TP53 without corresponding alterations of INK4a/ARF locus. In particular, ARF and not p16 appears significantly overexpressed in MIBC, and mainly localized in the nucleolus of patients-derived bladder cancerous cells [147], a feature that correlates with the tendency to develop chemoresistance. Using a mouse model in which the ARF coding region was conditionally ablated in the bladder tissue of Trp53 -/- /Pten -/- mice, the authors showed that Arf wild-type tumors were markedly resistant to treatment with cisplatin compared with the Arf -null counterpart.…”
Section: Arf Has Pro-oncogenic Functionsmentioning
confidence: 99%
“…Interestingly, a substantial percentage (35%) of MIBCs, displays mutant TP53 without corresponding alterations of INK4a/ARF locus. In particular, ARF and not p16 appears significantly overexpressed in MIBC, and mainly localized in the nucleolus of patients-derived bladder cancerous cells [147], a feature that correlates with the tendency to develop chemoresistance. Using a mouse model in which the ARF coding region was conditionally ablated in the bladder tissue of Trp53 -/- /Pten -/- mice, the authors showed that Arf wild-type tumors were markedly resistant to treatment with cisplatin compared with the Arf -null counterpart.…”
Section: Arf Has Pro-oncogenic Functionsmentioning
confidence: 99%
“…All the animal experiments were conducted in compliance with CIEMAT guidelines, and approved by the Animal Welfare Department of the Comunidad de Madrid (Spain; PROEX 088-15, PROEX 183/15). Palbociclib and CDDP concentrations were chosen based on previously published data (14,15). After 15-30 days of treatment, mice were sacrificed and tumors were collected and processed.…”
Section: Tumor Xenografts and Transgenic Mouse Modelmentioning
confidence: 99%
“…Cisplatin is a platinum-based compound that exerts a broad spectrum of anti-tumor activities in various cancers via the formation of both inter- and intra- strand DNA adducts 4. However, intrinsic or acquired cisplatin resistance severely attenuates its therapeutic potential 5. The molecular drivers of cisplatin resistance are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%